Efficiency of color sticky traps in the insect capture of leafy vegetable - Bravo-Portocarrero, Rosario (2020)
In vegetables, as well as in other crops, insect pests cause yield losses, therefore, in the search to solve this problem and as part of an integrated pest management, this research aimed to evaluate trapping efficiency of sticky traps for phytophagous insects present in leafy vegetables. For this, traps of different colors were installed in chard crops (Beta vulgaris), cabbage (Brassica oleracea var. capitata), lettuce (Lactuca sativa) and coriander (Coriandrium sativum). The most common insects were thrips (Frankliniella sp.), Cicadelline leafhoppers (Borongonalia sp.), aphids (Myzus persicae and Myzus sp.), psyllid (Russelliana sp.) and root fly (Diptera-Anthomiidae). Light blue and white sticky traps, show capture efficiency for thrips in 30% and 28% respectively; adults of root fly were captured with efficiency of 23% of all insects on white traps and 17% on light blue traps. Yellow traps efficiently attract aphids by 26% and by green traps by 20%; the greatest attraction of cicadelline leafhoppers occurred on orange (21%) and yellow (20%) traps; for psyllids, traps of orange, green and yellow colors show captures of 21%, 20% and 18%, respectively. The lower efficient traps were pink, red and black, with caught of 10%, 8% and 6%, respectively.